2021
DOI: 10.3390/ani11113185
|View full text |Cite
|
Sign up to set email alerts
|

A Survey Study of Veterinary Student Opinions and Knowledge about Pet Reptiles and Their Welfare

Abstract: Exotic pet medicine is rapidly evolving, with reptiles becoming increasingly popular pet animals. Yet, there are only a few literature reports on veterinary perception of reptiles kept as pets. The aim of the study was to assess opinions and knowledge of the Croatian veterinarians-to-be about pet reptiles and their welfare. The questionnaire survey was conducted in the academic year 2019–2020 and included students of all six years of the integrated undergraduate and graduate study at the Faculty of Veterinary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…The poor hygienic management of terrariums could be the cause behind this, mainly in pet shops where staff are usually busy and lack the necessary time to properly tend to cleanliness. Thus, ensuring proper cleaning and disinfection is difficult [30,31]. This situation encourages the persistence of MDR strains within shops, affecting consecutive batches of reptiles.…”
Section: Discussionmentioning
confidence: 99%
“…The poor hygienic management of terrariums could be the cause behind this, mainly in pet shops where staff are usually busy and lack the necessary time to properly tend to cleanliness. Thus, ensuring proper cleaning and disinfection is difficult [30,31]. This situation encourages the persistence of MDR strains within shops, affecting consecutive batches of reptiles.…”
Section: Discussionmentioning
confidence: 99%
“…Ostovic and collaborators surveyed in the academic year 2019–2020 veterinary students from Zagreb (Croatia) from different courses related to the veterinary medicine of reptiles. The study also revealed the need to invest in efforts to update the veterinary curriculum to introduce additional education for future Croatian veterinarians in reptile medicine since, in addition to clinical practice, this problem has implications for the health and safety of humans and other animals, as well as for the protection of the environment [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some of the vendors provide brief information in flyers and on container labels, where the buyer will find basic information about the species and help them meet specific husbandry requirements for species. For animal well-being, it should be assumed that potential new owners have generalized deficiencies in knowledge of the biology and breeding of exotic animals; thus, the transfer of basic knowledge should take place at the time of handing over the animal to a new owner [70][71][72]. Purchasing exotic pets without prior substantive knowledge can be motivated by status factors, narcissistic and borderline personality traits, ostentation, social recognition, conformism and materialistic indulgence, or done on impulse [9,67,73,74].…”
Section: Discussionmentioning
confidence: 99%